Sustainable Management of Mealybugs Maconellicoccus hirsutus in Grapes (Vitis vinifera) and Influence of Environmental Factors in Growth of the Pest - Pant, Janak; Prava Dawadi; Devkota, Bikalpa (International Journal of Applied Sciences and Biotechnology, 2025)
The efficacy of different pesticides in grape mealybugs Maconellicoccus hirsutus have not been investigated clearly in Nepal. This research intended to outreach effectiveness of possible pesticides in mealybugs M. hirsutus infesting grape vines. The research was conducted in Chandannath, Jumla district in the selected grape vineyards (Vitis vinifera). Four treatments namely, insecticide (soil drenching of Imidacloprid 200 SL @1.5 ml/l of water/plant), botanical pesticide (neem oil Azadirachta indica 2 tablespoon mixed with one quarter water and few drops of dish soap), entomopathogenic fungi (Beauveria bassiana WP with 2 × 108 cfu/g)), and untreated control were applied in the research plots to investigate their efficacy in the mealybugs M. hirsutus.At the minimum temperature of 10°C the average numbers of mealybugs M. hirsutus were 120, which then gradually increased to 300 and 470 at 11 and 12°C respectively. At 19 and 20°C the insect population rose to 2400 and 300 on an average respectively. With increase in relative humidity (%) from 50 to 60 the population of mealybug M. hirsutus also increased to 4100 from 1100 on an average. The temperature and relative humidity have non-significant and significant relationship respectively with the population of mealybug M. hirsutus in grape vines. Imidacloprid has highest effectiveness in comparison to neem oil, B. bassiana, and untreated control, though it has numerous negative consequences including growth of insecticide resistance in the pest population. Therefore, Imidacloprid would be the best control strategy for mealybug M. hirsutus, however, neem oil (Azadirachta indica) could be the most efficient and sustainable option for managing mealybug M. hirsutus in grape vineyard.Int. J. Appl. Sci. Biotechnol. Vol 13(1): 58-64.